Peningkatan Kapasitas Masyarakat dalam Pengelolaan Sampah Organik melalui Pelatihan Kompos di Dusun Bakung, Kabupaten Bantul - Khalda Putri Salsabila; Fitri Ainun Ridha; Tiara Rahmawati; Alfin Dwi Meytra; Clarissa Radhi Putri Azahra; Ibnu Rois; Heru Subaris Kasjono (Poltekkes Kemenkes Yogyakarta, 2024)
Household organic waste has become a pressing environmental health issue, particularly in areas with limited centralized waste management systems. The temporary closure of the Piyungan landfill has exacerbated this problem, including in Bakung Hamlet, Bantul Regency. This community service program aimed to improve community knowledge and skills in managing organic waste through composting practices. The intervention employed a participatory community empowerment approach, consisting of health education, problem identification surveys, and composting training. The target participants included local youth and community members actively involved in environmental activities. Program evaluation was conducted using pretest–posttest assessments and skill observations. The results indicated an improvement in participants’ knowledge and practical skills in organic waste management, along with initial behavioral changes in waste sorting and utilization. Prior to the intervention, most households disposed of organic waste by burning; however, participants demonstrated increased awareness of environmentally friendly alternatives after the program. The activity also succeeded in establishing youth cadres capable of conducting follow-up education within the community. Overall, this program contributed to strengthening community capacity in waste management and promoting a cleaner and healthier environment.